O10.6 A longitudinal analysis of men who have sex with men's condom use and attitudes during HIV antiretroviral prevention scale-up. (14th July 2019) - Lachowsky, Nathan; Wang, Lu; Bacani, Nicanor; Armstrong, Heather; Olarewaju, Gbolahan; Card, Kiffer; Crosby, Richard; Roth, Eric; Hogg, Robert; Moore, David
Abstract : Background: Within British Columbia, men who have sex with men (MSM) comprise an increasing proportion of new HIV diagnoses (60% in 2016). We sought to identify temporal trends in condom-use and condom-related attitudes among MSM, especially in relation to antiretroviral-based prevention scale-up. Methods: A prospective biobehavioural cohort of sexually-active MSM in Metro Vancouver were recruited using respondent-driven sampling (RDS). Every six months, participants self-completed questionnaires. We analyzed temporal trends (6-month periods) in condomless sex (binary outcome) and condom-related attitudes (continuous outcomes) using 3-level generalized linear mixed model (visit; participant; RDS chain). Statistical interactions were tested between time and antiretroviral treatment/pre-exposure prophylaxis (PrEP) use. Results: Between 03/2015–02/2018, 520 participants (32.1% HIV-positive) completed 1861 study visits. Over time, reporting any condomless anal sex with an unknown/opposite status partner increased for HIV-negative men (OR=1.20, 95%CI:1.03–1.40) and decreased for HIV-positive men (OR=0.83, 95%CI:0.73–0.94). Correct Condom Use Self-Efficacy scale scores decreased among HIV-positive men (B=-0.296, p<0.001) but remained unchanged among HIV-negative men (p=0.167). Overall, Condom Barriers Experience subscale scores decreased, indicating more problems over time (B=-0.236, p<0.001). Other individual items indicated that fewer men reported they 'can always get condoms' (B=-0.023, p=0.003), 'always have condoms when I have sex' (B=-0.028, p=0.006), and 'can always ask sexual partners to use condoms' (B=-0.027, p=0.002). Over time, the ability to 'say no' to condomless sex increased among HIV-negative men using PrEP (B=0.172, p=0.023), but decreased among HIV-negative men not using PrEP (B=-0.049, p=0.001) (interaction, p=0.004). Conclusion: MSM reported changing condom experiences over time, including decreased condom access, availability, and norms. HIV-positive men had less condomless sex with serodiscordant partners and reported more difficulties using condoms over time. PrEP-using men reported greater agency to decline condomless sex; the opposite was true for other HIV-negative men. Innovations in individual and community-level condom promotion and interventions are needed, especially for HIV-negative men not using PrEP. Disclosure: No significant relationships.